Girl!Version: The feminist framework for regendered characters in fanwork. (1st March 2016) - Baker, Lucy
Regendering, where fan creators change the gender of an existing character as part of the adaptation, offers a deconstruction of gender via the simultaneous examination of the original character, and the manifestation of gender performance in the regendered cipher. It also highlights and then occupies the absence of non-male characters, an absence being identified by researchers and fans as endemic to mainstream media. An examination of elements in commercial and non-commercial fanworks and paratexts, and the fannish engagement with those texts, reveals the methods and the motivation behind the regendering as a sort of praxis situated in the conflicts and complexities of the feminist theory and politics. It is also a manifestation of subversion and dissatisfaction – theorized by Jenkins and Sandvoss – with Butlerinfluenced understandings of gender performance and oppositional heterosexuality. This analysis and overview provides the foundation for a theory of how regendering works both with and against the hegemony of the media depiction of women, sexuality and sex.